Cell-based multi-substrate assay coupled to UHPLC-ESI-MS/MS for a quick identification of class-specific HDAC inhibitors. (1st November 2016) - Zwick, Vincent; Simões-Pires, Claudia; Cuendet, Muriel
Abstract: Histone deacetylases (HDAC) are involved in several diseases including cancer, cardiovascular and neurodegenerative disorders, and the search for inhibitors is a current topic in drug discovery. Four HDAC inhibitors have already been approved by the FDA for cancer therapy and others are under clinical studies. However, the clinical utility of some of them is limited because of unfavorable toxicities associated with their broad range of HDAC inhibitory effects. Toxicity could be decreased by using HDAC inhibitors with improved specificity. To date, the most popular screening assays are based on fluorescence-labeled substrates incubated with an enzymatic source (cells extracts or recombinant isoforms). Here, we describe a high-throughput cell-based UHPLC-ESI-MS/MS assay able to rapidly predict activity against HDAC1 and HDAC6 in a cell environment. This method is predicted to be a useful tool to accelerate the search for class-selective HDAC inhibitors in drug discovery.